THE EFFECT OF VALUE ADDED TAX, LUXURY GOODS SALES TAX, INCOME ON MOTOR VEHICLE CONSUMER PURCHASING POWER - I Dewa Ayu Trisna Payani; Ni Luh Supadmi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to determine the effect of value added tax, sales tax on luxury goods and taxpayer income on the purchasing power of motor vehicle consumers. The location of this research is at the Badung Regency SAMSAT Office, the number of samples used is 100 taxpayers using the accidental sampling method. Data collection was carried out by distributing questionnaires. The collected data was then analyzed using multiple linear regression analysis. The research results show that value added tax, sales tax on luxury goods and taxpayer income have a positive effect on the purchasing power of motor vehicle consumers. The theoretical implication in this research is that it is able to provide additional information regarding the influence of value added tax, sales tax on luxury goods and taxpayer income on the purchasing power of motor vehicle consumers which is linked to the theory of the principles of purchasing power and prestige. The practical implication of this research is that it can make a positive contribution to the Bali Provincial Government and taxpayers.